2011
DOI: 10.1523/jneurosci.4597-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Neural Control of Cough and Cough Suppression in Humans Using Functional Brain Imaging

Abstract: Excessive coughing is one of the most common reasons for seeking medical advice, yet the available therapies for treating cough disorders are inadequate. Humans can voluntarily cough, choose to suppress their cough, and are acutely aware of an irritation that is present in their airways. This indicates a significant level of behavioral and conscious control over the basic cough reflex pathway. However, very little is known about the neural basis for higher brain regulation of coughing. The aim of the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
165
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(181 citation statements)
references
References 39 publications
5
165
1
2
Order By: Relevance
“…Preprocessing and analysis of functional images was performed using standard procedures with FEAT, version 4.1.9 (75). Regressors for rating, liquid in the mouth, and swallowing events were included in the model, which also incorporated the confound regressors related to head motion and physiological noise produced by respiratory maneuvers during swallowing (76,77). A regression analysis was performed for the oversated condition by using the mean of each participant's effort and pleasantness ratings as independent regressors to explain brain activity during the preswallow period.…”
Section: Methodsmentioning
confidence: 99%
“…Preprocessing and analysis of functional images was performed using standard procedures with FEAT, version 4.1.9 (75). Regressors for rating, liquid in the mouth, and swallowing events were included in the model, which also incorporated the confound regressors related to head motion and physiological noise produced by respiratory maneuvers during swallowing (76,77). A regression analysis was performed for the oversated condition by using the mean of each participant's effort and pleasantness ratings as independent regressors to explain brain activity during the preswallow period.…”
Section: Methodsmentioning
confidence: 99%
“…It is still unclear which of these three receptors, individually or collectively, are responsible for the elicitation of the RC and precisely how they work together to regulate it (Canning, 2006;Haji et al, 2013). Mazzone, Cole, Ando, Egan, & Farrell (2011) investigated neurological control of VC, non-evoked suppressed coughing (where participants were instructed not to cough and coughing was completely suppressed) and evoked cough reflex (where participants were instructed to cough whilst breathing in capsaicin) in healthy individuals undergoing fMRI.…”
Section: Neurological Control Of Coughmentioning
confidence: 99%
“…Furthermore, VC is predominantly cortically controlled whereas RC is controlled by the rostral and caudal medulla (Mazzone et al, 2011). This implies that neurological impairment could result in very different outcomes for VC versus RC as shown by Fontana et al (1998) who found that RC was more impaired than VC in patients with Parkinson's disease.…”
Section: Reflexive Cough Versus Voluntary Coughmentioning
confidence: 99%
“…Distinct higher brain circuitry for facilitating and suppressing the cough reflex has been visualized by functional magnetic resonance imaging (fMRI) [22]. CHS is associated with hypersensitivity of the larynx and upper airway and is often diagnosed by clinical history [23] and sometimes through quantitative sensory testing such as with hypertonic saline challenge, transnasal laryngoscopy with odor provocation, and cough reflex sensitivity testing with capsaicin [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The most pronounced effect was a reduction in stimulus-induced brain deactivation following central sensitization. In cough, Mazzone et al [22] investigated the neural control of cough and cough suppression in healthy humans with capsaicin-evoked cough using fMRI. These studies have confirmed the existence of distinct higher brain circuitry for facilitating and suppressing the cough reflex and provide novel insights into the supramedullary control of cough in humans.…”
Section: Introductionmentioning
confidence: 99%